2022
DOI: 10.3389/fimmu.2022.1012594
|View full text |Cite
|
Sign up to set email alerts
|

cGAS/STING and innate brain inflammation following acute high-fat feeding

Abstract: Obesity, prediabetes, and diabetes are growing in prevalence worldwide. These metabolic disorders are associated with neurodegenerative diseases, particularly Alzheimer’s disease and Alzheimer’s disease related dementias. Innate inflammatory signaling plays a critical role in this association, potentially via the early activation of the cGAS/STING pathway. To determine acute systemic metabolic and inflammatory responses and corresponding changes in the brain, we used a high fat diet fed obese mouse model of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 87 publications
3
24
0
Order By: Relevance
“…In addition, a positive correlation was observed between the body weight and microglial numbers, indicating that increased obesity is associated with a greater number of hippocampal microglia. These findings align with our recent report where we show changes in hippocampal microglial activation as measured by microglial morphology after only 4 days using this model of HFD induced obesity and prediabetes [ 58 ]. Other have similarly shown that HFD causes robust changes in microglial activation as measured by changes in morphology [ 12 , 22 , 55 , 59 , 60 ], phagocytosis or phagocytic markers [ 12 , 22 , 60 ], and microglial numbers or density [ 12 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, a positive correlation was observed between the body weight and microglial numbers, indicating that increased obesity is associated with a greater number of hippocampal microglia. These findings align with our recent report where we show changes in hippocampal microglial activation as measured by microglial morphology after only 4 days using this model of HFD induced obesity and prediabetes [ 58 ]. Other have similarly shown that HFD causes robust changes in microglial activation as measured by changes in morphology [ 12 , 22 , 55 , 59 , 60 ], phagocytosis or phagocytic markers [ 12 , 22 , 60 ], and microglial numbers or density [ 12 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…ELISA was performed by the University of Michigan Immune Monitoring Core of the Rogel Cancer Center. Terminal IHC for analysis of hippocampal microglial infiltration was performed on cohort 3 hemi brains similar to previous [ 58 ]. In brief, following sacrifice, hemi-brains were dissected and fixed in 4% paraformaldehyde for a minimum of 48 h, then passed through a sucrose gradient.…”
Section: Cognitive Phenotypingmentioning
confidence: 99%
“…[15][16][17] The cGAS/STING system is one such innate inflammatory route connected to the cellular response to metabolic dysfunction. [18][19][20] In a mouse model of Parkinson's disease (PD) as well in the Substantia Nigra of human patients with PD, the activation of STING leads accumulation of α-synuclein and subsequent neurodegeneration and neuroinflammation. Mice deficient in STING were protected from loss of dopaminergic neurons while α-synuclein aggregates increase STING expression.…”
Section: S Ting In the Cn S And Neuro Inf L A M M At I O Nmentioning
confidence: 99%
“…23 These studies demonstrate a role for innate immune systems and the cGAS/STING pathway in mediating metabolic disequilibriuminduced CNS dysfunction. 18 In CNS injury, STING signaling is elevated and is involved in uncontrolled inflammatory processes such as that seen in traumatic brain injury (TBI), spinal cord injury (SCI), subarachnoid hemorrhage (SAH), and hypoxic-ischemic encephalopathy (HIE). However, the STING-regulated signaling activity that affects CNS damage remains unclear; together with cytokine production, STING signaling is implicated in cell death pathways such as autophagy, necroptosis, ferroptosis, and pyroptosis.…”
Section: S Ting In the Cn S And Neuro Inf L A M M At I O Nmentioning
confidence: 99%
See 1 more Smart Citation